PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA PENGURUS UAM FEB UNISMA 2019 - Ahmad Zaki Azzuhairi; Hadi Sunaryo; A. Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to determine the effect of organizational culture, work environment and motivation on the administrators of UAM FEB UNISMA, in this study the sample is the management of UAM FEB UNISMA, collecting data using questionnaires to administrators, analysis of the data used is validity test, reliability test, normality test , multiple linear analysis, statistical test f and statistical test t, the results of this study have a significant positive effect on organizational culture, work environment and motivation on the performance of UAM FEB UNISMA administrators, there is a significant influence of organizational culture on the performance of UAM FEB UNISMA administrators, there is a significant influence work environment towards the performance of UAM FEB UNISMA administrators, there is a significant effect of motivation on the performance of UAM FEB UNISMA administrators. Keywords: Organizational culture, Work environment, Motivation, the performance.